Expression of brain adiponectin in a murine model of transient cerebral ischemia - Shen, Lin-Hui (Int J Clin Exp Med, 2014)
Objective: Adiponectin is a hormone that is mainly secreted by fat cells. Adiponectin has anti-inflammatory and anti-atherosclerotic effects, and a protective effect against ischemic brain injury, but the level of expression of adiponectin in brain tissue is unknown. In the current study, a mouse model of transient cerebral ischemia was used to determine the level of expression of adiponectin in ischemic brain tissue. Methods: Sixty CD-1 mice underwent transient middle cerebral artery occlusion. The level of expression of adiponectin in mouse brain tissues 1 hour, 4 hours, 1 day, 3 days, and 7 days, after cerebral ischemia/reperfusion injury were determined using a real-time quantitative polymerase chain reaction, Western blot, and immunohistochemistry. Results: The level of expression of adiponectin in mouse ischemic brain tissues increased after cerebral ischemia/reperfusion injury and was higher in the central area of ischemia than in the peripheral area. The level of expression of adiponectin occurred only in vascular endothelial cells. There was no significant change in the level of expression of adiponectin mRNA in brain tissue pre- and post-ischemia/reperfusion injury. Conclusion: After cerebral ischemia/reperfusion injury, adiponectin accumulated in the vascular endothelial cells of ischemic brain tissues, and non-endogenous adiponectin was generated. Circulating adiponectin accumulated in ischemic brain tissues through its role in adhering to damaged vascular endothelial cells.